1997
DOI: 10.1144/gsjgs.154.6.1001
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic fault activity in Hong Kong: evidence from seismic events and thermoluminescence dating of fault gouge

Abstract: Hong Kong lies within a major NE-trending fault zone that has been reactivated during several tectonic episodes since the Palaeozoic. Three main faults sets are recognized in Hong Kong: a dominant NE-trending set, an ENE- varying to E-trending set and a subordinate NW-trending set. Over the last 1000 years, within a distance of 350 km of Hong Kong, there have been about 40 earthquakes with magnitudes of over 4.75, and of these 11 had magnitudes of over 6.0. Microseismic events in the last ten years are diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Friction-generated heat has also been detected using zircon He thermochronometry (Maino et al, 2015) and ferrimagnetic resonance signals via ESR (Fukuchi et al, 2007). Luminescence and ESR signals of quartz and feldspar can be reset within fault gouge (Ding & Lai, 1997;Fukuchi, 2001;Lee & Yang, 2007;Mukul et al, 2007;Singhvi et al, 1994;Spencer et al, 2012), although it is challenging to 10.1029/2018TC005312 Tectonics empirically reproduce signal resetting under equivalent conditions in the laboratory (e.g., Fukuchi & Imai, 1998;Toyoda et al, 2000).…”
Section: Fault Zone Processes: Earthquakes Creep and Geofluid Flowmentioning
confidence: 99%
“…Friction-generated heat has also been detected using zircon He thermochronometry (Maino et al, 2015) and ferrimagnetic resonance signals via ESR (Fukuchi et al, 2007). Luminescence and ESR signals of quartz and feldspar can be reset within fault gouge (Ding & Lai, 1997;Fukuchi, 2001;Lee & Yang, 2007;Mukul et al, 2007;Singhvi et al, 1994;Spencer et al, 2012), although it is challenging to 10.1029/2018TC005312 Tectonics empirically reproduce signal resetting under equivalent conditions in the laboratory (e.g., Fukuchi & Imai, 1998;Toyoda et al, 2000).…”
Section: Fault Zone Processes: Earthquakes Creep and Geofluid Flowmentioning
confidence: 99%
“…Hong Kong lies within the southeast margin of the South China block. Seismological and geological studies have demonstrated that the level of seismicity in Hong Kong is low to moderate but the question of whether there is any fault activity in or near Hong Kong presently is still controversial [5,6] . Geodetic techniques, such as EDM and GPS, are most effective to be used for monitoring crustal deformation.…”
Section: Introductionmentioning
confidence: 99%